Peranan Badan Pertimbangan Jabatan dan Kepangkatan dalam Penyelenggaraan Mutasi Pegawai Negeri Sipil di Kabupaten Halmahera UtaraPeranan Badan Pertimbangan Jabatan dan Kepangkatan dalam Penyelenggaraan Mutasi Pegawai Negeri Sipil di Kabupaten Halmahera Ut - Kapita, Mutlaben; Pangkey, Masje Silija; Pombengi, Jericho Denga (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The research objective was to determine the role of the Advisory Board Position and Rank in the administration of personnel transfers structural position as mandated by Law No. 43 of 1999 on changes to Law No. 8 of 1974 About the Fundamentals of Civil Service that in the appointment, transfer and dismissal of employees must be based principles of professionalism of employees which include competence, work performance, and level rank Civil Servant. To determine the role of the Advisory Board Positions and Ranks in the implementation of personnel transfers structural position, the research method used is qualitative method, which is where the researcher as a key instrument in the study consisted of 13 informants. The role of the Advisory Board Position and Rank in the administration of personnel transfers in North Halmahera is his duty to give consideration and advice in terms of personnel transfers by taking into account the competence, performance and level of rank is not everything is going well. Because the data is based on mutations in January that there are many employees who are placed not in accordance with the principles of The riht Man On The Right Place even exist in mutation employee has concurrently. And so is the implementation of personnel transfers more attention to long term in-service tasks, proximity or kinship relationships compared with competence, work performance and level rank for employees transferred. And there is recognition of employees that once issued Decree of the new regent he knows himself in mutasikan on new positions. To avoid the Spoil System Advisory Board Positions and Ranks need to cooperate with an independent assessment team and has experience in assisting the selection of employees transferred. And to the results of the session of the Advisory Board Positions and Ranks recommended to the Regional Personnel Officer in a transparent manner for the sake of accountability in policy mutation. Similarly, to get a good employee performance, then it should in the implementation of personnel transfers expected consideration Agency Position and Rank refers to Law Number. 43 of 1999 on changes to Law No. 8 of 1974 About the Fundamentals of Civil Service which is technically explained that the appointment or removal shall be in accordance with the Civil Servants professionalism. Keywords: The role of the Advisory Board Position. Rank in the Implementation of Civil Servants Mutation.